The Implementation of Translanguaging in Ontario Early Childhood Education Curriculum: A Literature Review - Chuan Liu (Canadian Society for Studies in Education, 2023)
Albeit the linguistically diverse settings in Ontario, language policies in schools that English and/or French as the only instructional language(s) departmentalize language repertories of bi/multilingual students. In response to the surging demand for bi/multilingual students, translanguaging is advocated to appreciate students' fund of knowledge and their full language repertoires. This study adopts sociocultural and critical theory lenses to investigate the incorporation of translanguaging in instructional design in Ontario's early childhood education. This paper reviews relevant literature about translanguaging in Ontario. The findings demonstrated that translanguaging should be a critical component in multilingual classrooms to facilitate students with meaning-making and emancipation of individual voices in Ontario. There is a need for the incorporation of translangauging in teacher education and professional development.